Teacher Readiness for Augmented-Reality Health Education in Elementary Physical Education: A Community-Engaged Evaluation of the BIPINIPAR Interactive Book in Surabaya - Junaidi Budi Prihantono; Dwi Lorry Juniarisca; Arifah Kaharina; Aby Nugrah Septanto; Novadri Ayubi (Universitas Malahayati Lampung, 2026)
ABSTRACT Elementary physical education must translate abstract health messages about hygiene, physical activity, safety, and healthy living into concrete learning experiences. This community-engaged study evaluated BIPINIPAR, an augmented-reality interactive health-education book for Indonesian elementary Physical Education, Sport, and Health (PJOK), by examining changes in teacher readiness and perceived implementation feasibility. A one-group pre–post evaluation was conducted with 44 valid responses from elementary-school physical education teachers or education practitioners in Surabaya. Five readiness indicators were rated before and after training. Because one baseline item used a shorter scale than its paired post-training item, all readiness indicators were min–max normalized to a 0–100 metric. Program appraisal was measured with nine 1–5 items, and open-ended comments were coded thematically. Overall readiness increased from 86.14 ± 18.03 to 91.21 ± 11.94, with a mean gain of 5.08 percentage points (95% CI 1.14–9.01; p = .013; Cohen's dz = 0.39). Gains were strongest for AR-book knowledge, AR-use skill, and confidence to teach with AR. Program appraisal was very high (mean 4.81/5), with 99.5% of item-level responses in the high or very high range. BIPINIPAR is best understood as a teacher-mediated implementation-readiness intervention that can support AR-enhanced physical education, health education when accompanied by pedagogical training and sustained classroom support. Keywords: Augmented Reality, Interactive Health Education Book, Elementary Physical Education, Teacher Readiness, Community-Engaged Learning.